Factors associated with Autumn rearing of duck broods in temperate North America - Krapu, G L; Brandt, D A; Beiser, J A (Wildfowl, 2001)
Dabbling ducks Genus Anas occasionally nest during mid- and late summer in the Prairie Pothole Region (PPR) of midcontinent North America but little information is available on their Autumn-reared broods or those of other duck genera. Densities, species composition, and wetland habitat use by Autumn reared duck broods (age classes I and II) were determined on randomly distributed transects on a 3,735 km^2 study area in eastern North Dakota. Brood densities (SE) averaged 0.380.08, 0.300.08 and 0.230.10 broods km^-2 during 1993-95 with dabbling ducks accounting for 70, 44, and 9%, and diving ducks 30, 54, and 91% of sighted broods. The principal species were Blue-winged Teal Anas discors, 21%; Gadwall A. strepera, 11%; Mallard A. platyrhynchos, 7%; Redhead Aythya americana, 13%, and Ruddy Duck Oxyura jamaicensis, 35%. Of Blue-winged Teal and Mallard broods, 67% of each were located on seasonal ponds, and 50, 56, and 59% of Gadwall, Redhead and Ruddy Duck broods were on semi-permanent ponds. Interspecific variation in numbers of Autumn-reared broods resulted, in part, from intrinsic differences among species in capacity to nest during mid- and late summer. Survival of thousands of class I and II dabbling duck broods to mid-September during 1993-94 probably resulted from a combination of factors including an abundance of seasonal ponds, low rainfall, and limited cold weather through mid-September when brood surveys were conducted. Redheads and Ruddy Ducks do not terminate breeding under long daylengths in late spring so summer nesting accounts for a much larger portion of the annual nesting effort than in dabbling ducks except under drought conditions when ducks generally terminate reproduction by midspring.